Transformative Agenda of Teacher Education: A Case of Delhi University - Kaur, Parminder (Voices of Teachers and Teacher Educators, 2020)
Teachers possess a highly significant position in the educational sphere and therefore no education system can be aloof from these significant stakeholders in order to realize its envisioned goals. Considering the symbiotic relationship between education and the teacher education sphere, the Indian education system has continuously reformed and reflected on its intent in order to cater to the demands of the society through an array of educational policies and plans marking a long history since the pre-independence era till the present times. If the teachers possess such an indispensable role, so does their education holds immense vitality. This paper is an attempt to recognize and reflect on the practical undertaking of one of the promising teacher education course in Delhi University. It also responds to the dire need of professional preparation of teachers at the very preliminary stage and therefore meet the rising demands of the budding professionals in the education arena. This descriptive type qualitative paper presents a case of one such pre-service teacher education course, B.El.Ed. (Bachelors in Elementary Education) presently transacted in Delhi University that re-conceptualized the overall scenario of nation’s teacher education with its onset. The course holds a unique identity with its distinct intent, structure and function altogether that cater to the needs of the teacher education system efficiently. For better assimilation of the topic the paper is well dissected into various subheads that provides an actual essence of the topic and discuss the case of B.El.Ed. in particular. The sub themes of the paper unfolds the integrity of the professional preparation of teachers in the present times and thus, provides enriched understanding of the educational concern. The rich exposure and experiences of the participants of the research i.e. teacher educators, course leaners and course graduates lends enough plausible insights about the course.